Parallel programming of exogenous and endogenous components in the antisaccade task - Massen, Cristina (The Quarterly journal of experimental psychology. A, Human experimental psychology, 2004)
In the antisaccade task subjects are required to suppress the reflexive tendency to look at a peripherally presented stimulus and to perform a saccade in the opposite direction instead. The present studies aimed at investigating the inhibitory mechanisms responsible for successful performance in this task, testing a hypothesis of parallel programming of exogenous and endogenous components: A reflexive saccade to the stimulus is automatically programmed and competes with the concurrently established voluntary programme to look in the opposite direction. The experiments followed the logic of selectively manipulating the speed of processing of these components and testing the prediction that a selective slowing of the exogenous component should result in a reduced error rate in this task, while a selective slowing of the endogenous component should have the opposite effect. The results provide evidence for the hypothesis of parallel programming and are discussed in the context of alternative accounts of antisaccade performance.